Comparison of the effects of alfentanil and remifentanil on postoperative cognitive functions [Alfentani̇l ve remi̇fentani̇li̇n postoperati̇f kogni̇ti̇f fonksi̇yonlar üzeri̇ne etki̇leri̇ni̇ n karşilaştirilmasi] - (:unkn) unknown (My University, 2010)
Objective: The aim of this study was to investigate the effects of alfentanil and remifentanil with propofol on peroperative hemodynamic parameters, recovery and cognitive functions in early postoperative period of the patients undergoing elective mastectomy. Method: Sixty patients, aged between 20-70 years, ASA status I-III, undergoing mastectomy were randomised into two groups (n=30). Standardized mini mental test (SMMT) was performed to all patients the night before the surgery. In all patients induction of anesthesia was performed by 2 mg kg-1 propofol. In the 1st group after 10 μg kg-1 iv bolus, alfentanil was infused 1.5 μg kg-1 min-1, in the 2nd group after 1 μg kg-1 iv bolus, remifentanil was infused 0.2 μg kg-1 min-1. For anesthesia maintenance propofol infusion was used in all patients, first 10 minutes 12 mg kg-1 h-1, the 2nd 10 minutes 9 mg kg-1 h-1 thereafter 6 mg kg-1 h-1. Alfentanil and remifentanil infusions were discontinued 15 minutes and 5 minutes before the end of surgery respectively and propofol infusion was stopped at the end of the surgery. Hemodynamic parameters, sedation scores and side effects were evaluated during postoperative 15 minutes with 5 minute intervals. SMMT was performed at the 1st and 3rd postoperative hours. Statistical analysis were made with two-way ANOVA for comparison of repeated measurements, with one-way ANOVA for comparisons between the groups and with Student-Newman-Keuls test for posthoc comparison (p<0.05). Results: The sedation scores of remifentanil group in postoperative 5th and 10th minutes are significantly lower than those of alfentanil group (p<0.05). Although preoperative SMMT values of groups were similar, the scores of alfentanil group were significantly lower than those of remifentanil group in the 1st hour postoperatively (p<0.001). Conclusion: We concluded that in patients undergoing mastectomy, remifentanil infusion could be preferred as the drug of choice during TIVA with propofol rather than alfentanil as cognitive functions and level of consciousness are less disturbed during early postoperative period.
Keywords: Alfentanil; Postoperative cognitive functions; Remifentanil